Personality, work-life balance, hardiness, and vocation: A typology of nurses and nursing values in a special sample of English hospital nurses - Christopher Bagley; Mahmoud Abubaker; Alice Sawyerr (Administrative Sciences, 2018)
This initial report of a longitudinal study of 192 English hospital nurses measured Nursing Values (the 6Cs of nursing); Personality, Self-Esteem and Depression; Burnout Potential;Work-Life Balance Stress; "Hardy Personality"; and Intention to Leave Nursing. Correlational, component, and cluster analysis identified four groups: "The Soldiers" (N = 79), with medium scores on most measures, who bravely "soldier on" in their nursing roles, in the face of numerous financial cuts to the National Health Service, and worsening nurse-patient ratios; "Cheerful Professionals" (N = 54), coping successfully with nursing roles, and a variety of challenges, in upwardly mobile careers; "High Achievers" (N = 39), senior nurses with strong profiles of a "hardy personality", and commitment to fundamental nursing values; and "Highly Stressed, Potential Leavers" (N = 20), with indicators of significant psychological distress, and difficulty in coping with nursing role challenges. We have initiated a program of co-counselling and social support for this distressed group, by nurses who are coping more successfully with multiple challenges. We discuss the role of nurse educators in fostering nursing values, developing and supporting a "hardy personality" and emotional resilience in recruits to nursing. This study is framed within the disciplinary approach of Critical Realism, which identifies the value basis for research and dialogue in developing strategies for social change. The importance of this research is that: (a) it is part of the new thrust in nursing research, applying Critical Realist theory and methodology to research on nursing stress; (b) it has established, through network sampling, a group of nurses who can be supportive of each other in their stressful careers; (c) it establishes the reliability and potential validity of a measure of core nursing values; (d) it is among the first studies in research on nursing stress, to use the humanizing methodology of moving from data analysis (description of "things"), to describing a typology of nursing stress and career progress (description of individuals).
Keywords: 350; nursing values; burnout; hardy personality; work-life balance; nursing stress; co-counselling; critical realism; nurse education; nurse-patient ratios